A compact, transportable 1550 nm ultra-stable laser system with Hertz linewidth - Zhang, Linbo; Wu, Mengfan; Gao, Jing; Liu, Jun; Fan, Le; Jiao, Dongdong; Xu, Guanjun; Dong, Ruifang; Liu, Tao; Zhang, Shougang (Applied physics. B, Lasers and optics, 2023)
We demonstrate a compact, transportable 1550 nm ultra-stable laser system with Hertz linewidth. The laser frequency is frequency stabilized to a vertically mounted, vibration-insensitive and high-fineness ultra-low-expansion (ULE) cavity with Pound-Drever-Hall (PDH) method. Optical boards designed by topology optimization and miniaturized optical component mounts without kinematic adjustment are designed to achieve a high level of integration and stability. The self-developed electronics and automatic locking module ensure fully automatic operation of the system. The entire ultra-stable laser system is highly integrated in a 19-inch 6 U chassis with a mass of about 35 kg. The prototype performs beat frequency comparison measurement with another ultra-stable laser system in the laboratory. The fractional frequency instability of a single system is achieved 4 × 10 - 15 at 1 s averaging time preliminarily, and the linewidth is 1.3 Hz. The portable ultra-stable laser system we developed is expected to have significant implications for precision measurement and other applications.